A slave in the White House : Paul Jennings and the Madisons - Taylor, Elizabeth Dowling (Palgrave Macmillan, 2012)
Chronicles the life of a former slave to James and Dolley Madison, tracing his early years on their plantation, his service in the White House household staff and post-emancipation achievements as a memoirist.